First report on the physicochemical and proteomic characterization of Proteus mirabilis outer membrane vesicles under urine-mimicking growth conditions: comparative analysis with Escherichia coli - González, María José; Navarro, Nicolás; Cruz, Erlen; Sánchez, Sofía; Morales, Javier O.; Zunino, Pablo; Robino, Luciana; Lima, Analía; Scavone, Paola (Frontiers in Microbiology, 2024)
IntroductionUropathogenic bacteria employ multiple strategies to colonize the urinary tract, including biofilm formation, invasion of urothelial cells, and the production of adhesins, toxins, and siderophores. Among the most prevalent pathogens causing urinary tract infections (UTIs) are Uropathogenic Escherichia coli and Proteus mirabilis. A notable feature of Gram-negative bacteria is their ability to produce outer membrane vesicles (OMVs), which play critical roles in bacterial survival, virulence, and host-pathogen interactions, including UTIs.MethodsIn this study, OMVs were isolated and characterized from two clinical strains, E. coli U144 and P. mirabilis 2,921, cultured in both Luria-Bertani broth and artificial urine.Result and discussionThe OMVs ranged in size from 85 to 260 nm, with the largest vesicles observed in artificial urine. Proteomic analysis allowed the identification of 282 proteins in OMVs from E. coli and 353 proteins from P. mirabilis when cultured LB medium, while 215 were identified from E. coli and 103 from P. mirabilis when cultured in artificial urine. The majority of these proteins originated from the bacterial envelope, while others were linked to motility and adhesion. Notably, the protein composition of OMVs varied depending on the growth medium, and proteins associated with zinc and iron uptake being more prominent in artificial urine, suggesting their importance in the urinary environment. Crucially, this is the first report to characterize P. mirabilis OMVs under different culture conditions, offering novel insights into the role of OMVs in UTI pathogenesis. These findings provide a deeper understanding of the molecular mechanisms by which OMVs contribute to bacterial virulence, establishing the foundation for potential therapeutic interventions targeting OMV-mediated processes in UTIs.